EFEKTIFITAS PEMBERIAN ZINC DALAM PENINGKATAN TINGGI BADAN (TB) ANAK STUNTING DI KABUPATEN PATI - Kasanah, Uswatun; Muawanah, Siti (Coping: Community of Publishing in Nursing; Vol 8 No 3 (2020): Oktober 2020, 2020)
Based on Riskesdas 2010, the prevalence of stunting in children under five in Indonesia reaches 35.7%. Stunting in children under five can be detrimental to physical development and affect low intelligence levels. Stunting is nine times more likely to have IQ scores below the average than children with normal nutritional status. One of the factors that directly influence stunting under five is the low intake of nutrients, especially energy, protein, iron, zinc, and calcium. Pati Regency is in second place in Central Java, where data from the Pati District Health Office as of April 2019 shows that the Jakenan Health Center area is ranked first. This study aimed to see the effectiveness of giving zinc (20 mg, twice a week for three months) to stunting children by comparing it to a control group, using a randomized pretest-posttest control group design. The total samples are 20 children. The study showed that there was a significant difference in the height of children who received zinc compared to the control group with a value of 0.001. The average increase height in the intervention group was 3.35 cm, while in the control group it was only 1 cm. The weight of children in the intervention group an average increase of 0.885 kg while in the control group was only 0.17 kg. This study provides information to stunting toddlers, especially those aged less than two years, twice a week as much as 20 mg regularly and consuming food as a source of nutrition for stunting toddlers.